Penerapan Metode Learning to Listen pada Gangguan Artikulasi Anak dengan Disaudia: Studi Kasus Tunggal - Adang Adang; Ramadhan Dalianto Putra; Aurora Dwi Amalia; Rika Aprilia Melati (Jurnal Terapi Wicara, 2023)
Dysaudia is a speech disorder associated with auditory feedback problems, which can occur due to hearing loss. Articulation is an important part of speech, and children with hearing problem need immediate help to improve their slow pronunciation skills due to hearing loss. One method of treating deaf children is to Learning to listen. By relying on the remaining hearing, this method aims to help children detect sounds and associate sounds with objects.